PREDICTORS OF ADVERSE CLINICAL COURSE OF CORONARY HEART DISEASE: THE RESULTS FROM DYNAMICAL OBSERVATION - E. V. Shlyakhto; Е. G. Sergeeva; О. А. Berkovich; S. N. Pchelina; М. I. Zarayskiy; Zh. I. Ionova; E. A. Polyakova; E. I. Baranova (Российский кардиологический журнал)
Aim. To reveal the molecular genetic predictors of adverse clinical course of coronary heart disease (CHD).Material and methods. A clinical genetic investigation performed, of 567 CHD patients, of those 199 underwent dynamic follow-up. Genotypes Pro12Pro, Pro12Ala, Ala12Ala of the gene PPAR-γ2, genotypes L162L and L162V gene PPAR-α, genotypes A603A, A603G, G603G gene of tissue factor were assessed with polymerase chain reaction and further restrictional analysis.Results. Carriage of the allele V162 gene PPAR-α and allele Ala12 gene PPAR-γ2 is associated with development of the following endpoints in CHD patients: recurrent angina, progression of heart failure, life-threatening arrhythmias, stroke and transient cerebral ischemia, myocardial infarction, fatal outcomes. Diabetes type 2 (DM2) in CHD patients was associated with the risk of adverse outcome 2,55 times. There was relation of DM2 in CHD patients and mortality. In CHD patients that undergone percutaneous coronary intervention and bypass grafting, the combination endpoint was registered rarer than in CHD patients with no interventions, with a decline of adverse CHD prognosis 2 times. The results can be explained by decreased inhibition of NF-kВ pathway in carriers of V162 and Ala12 genes PPAR-α and PPAR-γ2, that facilitates activation of the factors of immune inflammation and atherogenesis with further adverse outcomes of CHD. It is known that DM2 is a risk factor of CHD and its complications.Conclusion. Presence of DM2, carriage of allele V162 gene PPAR-α and allele Ala12 gene PPAR-γ2 is associated with adverse outcomes of CHD. In CHD patients with surgical revascularization of coronary arteries the risk of adverse CHD outcomes declined 2 times.